2012
DOI: 10.1016/j.jse.2011.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for revision surgery after humeral head replacement: 1,431 shoulders over 3 decades

Abstract: Objective Assess long-term risk of revision surgery and its predictors after undergoing humeral head replacement (HHR). Methods We used prospectively collected data from the Mayo Clinic Total Joint registry and other institutional electronic databases. Revision-free survival for HHR at 5-, 10- and 20-years was calculated using Kaplan-Meier survival analysis. We used univariate and multivariable-adjusted Cox regression analyses to examine the association of age, gender, body mass index (BMI), comorbidity asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 15 publications
3
19
2
1
Order By: Relevance
“… 31 Previous studies have reported unadjusted estimates of revision-free implant survival ranging from 89% to 92% at 10 years. 32 33 34 35 36 These published figures are similar to those found for our study population. The only published 20 year implant survival rates are from one centre (Mayo Clinic, MN) and indicate an 85% survival for 1431 humeral head replacements and 81% for 2588 total shoulder replacements.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… 31 Previous studies have reported unadjusted estimates of revision-free implant survival ranging from 89% to 92% at 10 years. 32 33 34 35 36 These published figures are similar to those found for our study population. The only published 20 year implant survival rates are from one centre (Mayo Clinic, MN) and indicate an 85% survival for 1431 humeral head replacements and 81% for 2588 total shoulder replacements.…”
Section: Discussionsupporting
confidence: 90%
“…The only published 20 year implant survival rates are from one centre (Mayo Clinic, MN) and indicate an 85% survival for 1431 humeral head replacements and 81% for 2588 total shoulder replacements. 32 33 These estimates are lower than the mean long term implant survival estimates for our study, but the mean age of patients in these studies was 63 and 65 years, respectively; substantially lower than our study mean age of 73 years. The proportion of men was also considerably higher, which might account for the higher reported revision rates.…”
Section: Discussioncontrasting
confidence: 75%
“…During this follow-up period, no revision of the components was seen in either the overweight group or the obese group. In contrast, Singh et al 38 reported obesity as a risk factor for higher revision rates after humeral head replacements after following a group of patients with >1400 shoulders in a twenty-year follow-up study.…”
Section: Discussionmentioning
confidence: 87%
“…Information about survival rates of hemiarthroplasty is sparse. A large institutional register study reported 26 revisions (7.5%) in 348 hemiarthroplasties used for osteoarthritis with a 10-year cumulative survival rate of 90.3% 28 . The Danish Shoulder Arthroplasty Registry reported 63 (7.5%) revisions in 837 resurfacing hemiarthroplasties with a 5 year cumulative revision rate of 12.1% 14 .…”
Section: Arthroplasty Typesmentioning
confidence: 99%